Destabilized property : property law in the sharing economy / Shelly Kreiczer-Levy. - Kreiczer-Levy, Shelly, 1979- (Law in context., 2019)
The sharing economy challenges contemporary property law. Does the rise of access render our conception of property obsolete? What are the normative and theoretical implications of choosing casual short-term use of property over stable use? What are the relational and social complications of blurring the line between personal and commercial use of property? The book develops a novel conceptualization of property in the age of the sharing economy. It argues that the sharing economy pushes for a mobile and flexible vision of engaging with possessions and, as a result, with other people. Property's role as a source of permanence and a facilitator of stable, long-term relationships is gradually decreasing in importance. The book offers a broad theoretical and normative framework for understanding the changing landscape of property, provides an institutional analysis of the phenomenon, discusses the social, communal, and relational implications of these changes, and offers guidelines for law reform.